A learning zone of one's own : sharing representations and flow in collaborative learning environments - Tokoro, Mario, 1947-; Steels, Luc (IOS Press, 2004)
This text is based largely on two workshops organized by Steels (Sony Computer Science Laboratory, Paris) in Portugal in 2002 and Spain in 2003, as part of a long-term effort initiated by Tokoro (Sony Computer Science Labs Inc., Tokyo) to stimulate multidisciplinary discussions aimed at improving education and learning for children and adults of al.